Rumination Assessment: A Managemental Tool for Dairy Cattle (Indian Journal of Animal Production and Management, 2024)
Rumination is the process of regurgitation, re-mastication, salivation and swallowing of ingesta. Cows  ruminate for approximately 504±93 min/day and a decrease in rumination time is typically important  sign that something is affecting ruminal function and cow well-being. Rumination activity mainly  occurs at night and during resting periods in the afternoon. Rumination can be detected by the several  methods viz. visual observation, video recording, nose band pressure signal, accelerometer ear-tags  and neck collar. The time that an animal spends ruminating is influenced by species, breed, physical  & chemical characteristics of the diet, health condition, feed intake and production level. More  roughage diet with long fibre increases the rumination time. Diets containing higher neutral detergent  fibre (%) resulted in increase in rumination time per kilogram of roughage ingested. Rumination time  decrease with increasing temperature humidity index. Rumination time significantly influence the milk  yield and milk composition and reproduction performance. Rumination time could be used to monitor  dairy cattle during calving, oestrous, and heat stress, as well as to detect diseases, heat stress,  transition cow disorders and subclinical ketosis in dairy cows.
Keywords: Rumination; Rumination Time; Cow; Production; Reproduction; Health